Stability of bioabsorbable fixation systems according to different locations of mandibular fracture: A three-dimensional analysis. Issue 8 (August 2021) - Song, In-Seok; Choi, Jimi; Kim, Seong Ryoung; Lim, Ho-Kyung; Lee, Jee-Ho
Abstract: This study aimed to elucidate whether the stability of an unsintered hydroxyapatite particles/poly-l -lactide (uHA/PLLA) system is comparable with that of titanium, according to different load-bearing areas of the mandible. The study included patients who underwent open reduction and internal fixation of the mandibular body, angle, or subcondylar fracture. The stability of uHA/PLLA systems was compared between the immediate and 6-month postoperative time points using three-dimensional cone-beam CT image analysis. The positional changes of each landmark were measured in three-dimensional (3D) coordinate systems using simulation software. Among 36 patients, there were more displacements of the landmarks between the immediate and 6-month postoperative time points after subcondylar fracture reduction than after body or angle fracture reductions. Strong upward displacements of the landmarks after subcondylar fracture reduction were found in the lateral pole [mean (SD) = 1.75 (3.16), p -value = 0.003] and medial pole [mean (SD) = 1.64 (2.50), p -value = 0.024], but not in the center. Subgroup analyses revealed similar unstable results in males on the condylar landmarks after subcondylar fracture reduction. There were tendencies for lateral displacement of the coronoid process in the body fracture group [mean (SD) = 0.8 (0.83)] and angle fracture group [mean (SD) = 0.75 (0.58)] postoperatively ( p -value = 0.01). This study concluded that bioresorbable osteosynthesis can be recommended for body or angle fractures, while the indication for subcondylar fractures is less clear.